Third-Generation Autologous Chondrocyte Implantation at the Knee Joint Using the Igor Scaffold: A Case Series With 2-Year Follow-up. Issue 1 (22nd January 2021) - Zak, Lukas; Kleiner, Anne; Albrecht, Christian; Tichy, Brigitte; Aldrian, Silke
Background: For large, locally restricted cartilage defects in young patients, third-generation matrix-supported autologous chondrocyte implantation (ACI) with a variety of scaffolds has shown good mid- to long-term results. Purpose/Hypothesis: This study aimed to monitor the clinical and radiological outcomes of patients who received ACI at the knee joint using the Igor scaffold (IGOR–Institute for Tissue and Organ Reconstruction) at 2-year follow-up. Our hypothesis was that there would be improvements in postoperative subjective scores and cartilage repair tissue quality. Study Design: Case series; Level of evidence, 4. Methods: A total of 21 patients (12 male and 9 female) were available for 2-year follow-up after third-generation ACI using the Igor scaffold. All were clinically assessed using the Knee injury and Osteoarthritis Outcome Score (KOOS), Tegner Activity Scale, Brittberg score, International Knee Documentation Committee (IKDC) Subjective Knee Form, Noyes Sports Activity Rating Scale, and visual analog scale for pain. For morphological evaluation, the magnetic resonance observation of cartilage repair tissue (MOCART) and MOCART 2.0 scores were calculated using 3-T magnetic resonance imaging performed at 3, 6, 12, and 24 months postoperatively. Results were compared between baseline and 24 months postoperatively. Results: After 2 years, the clinical and radiological scores showed good to excellent results in the majority of patients. On the IKDC, 10 patients were graded as excellent, 4 as good, 5 as fair, and 2 as severe; on the KOOS, 7 patients were graded as excellent, 8 as good, 4 as fair, and 2 as severe. From baseline to latest follow-up, visual analog scale pain scores decreased from 5.6 ± 3.2 (mean ± SD) to 1.5 ± 2; KOOS results increased from 51 ± 20.7 to 75.2 ± 15.4; and the Tegner score improved from 2.2 ± 1.8 to 4.3 ± 1.3. The MOCART and MOCART 2.0 scores were comparable at 2-year follow-up, with mean values of 74 ± 10 and 78 ± 13, respectively. Satisfactory filling and integration were found in 90.5%. Overall, 16 of 21 patients (76.1%) were satisfied with the surgery and would undergo the procedure again. Conclusion: Third-generation ACI using the Igor scaffold showed improvements in clinical and radiological results that were comparable with other scaffolds for patients with large traumatic or degenerative cartilage defects. Patients reported a decrease in pain and an increase in activity, with the majority reporting good results.